Prevalence, enumeration, and pheno- and genotypic characteristics of Listeria monocytogenes isolated from raw foods in South China - Chen, Moutong; Wu, Qingping; Zhang, Jumei; Wu, Shi; Guo, Weipeng (Frontiers in Microbiology, 2015)
Listeria monocytogenes is an important foodborne pathogen that can cause serious illness in immunocompromised individuals, pregnant women, the elderly, and newborns. The aim of this study was to: (i) evaluate the prevalence and contamination level (most probable number, MPN) of L. monocytogenes in 567 retail raw foods (fishery products, n=154; raw/fresh meat, n=123; frozen foods, n=110; edible fungi, n=108; vegetables, n=72) collected from South China and (ii) to gain further knowledge on the phenotype and genotype distributions of this important foodborne pathogen. Approximately 22% of the samples were positive for L. monocytogenes. The contamination levels were between 0.3 and 10 MPN/g in 75.0%, between 10 and 100 MPN/g in 11.0% and less than 100 MPN/g in 14.0% of the countable samples. Five serogroups were identified among the177 foodborne L. monocytogenes isolates, with1/2a-3a (42.4%) and1/2b-3b (26.0%) serogroups being the most dominant. Serogroup I.1 and II.2 were only found in the edible mushrooms, while serogroup III was dominant in the fishery products, suggesting that specific serogroups of L. monocytogenes may have distinct ecological niches. Ten (5.6%) L. monocytogenes isolates exhibited multidrug resistance. Genetic relatedness analysis revealed the absence of distinct associations between specific food types, antibiotic resistance, serogroups, and genetic diversity. The present study provided the first baseline data on the prevalence, contamination level, and characteristics of L. monocytogenes isolated from raw foods in South China. Some multidrug resistant strains belonged to the epidemiologically important serogroups (I.1 and II.1), implying a potential public health risk. In addition, these findings also provide basic information for the Chinese food safety associated authorities to draft appropriate standards to control L. monocytogenes contamination and improve microbiological safety of raw foods.